Exploring employee preferences for the Farm Credit System incentive program - Crider, Autumn Marie (Kansas State University, 2012)
The purpose of this thesis was to examine the relative efficacy of the incentive plan for loan officers within Farm Credit of the Virginia’s, ACA (FCV). The purpose of FCV’s incentive plan includes promoting firm financial growth and stability, employee retention, and encouraging teamwork. Incentive plans are important financial decisions for companies and these plans have upside potential and downside risk that should be considered in the decision making process. A literature review was conducted to analyze incentive practices and management theory in addition to a review incentive plans from other Farm Credit associations. A survey was also conducted to understand loan officer perceptions of the current incentive plan at FCV. The results of the survey provide insight into employee perceptions about job satisfaction, intrinsic motivation, extrinsic motivation, organizational commitment, understanding of the incentive plan, and timing of incentives. Finally, observations with regards to potential improvement in the incentive plan were provided.
Keywords: Incentives; Organizational commitment; Job satisfaction; Business (0310); Psychology (0621)